Manajemen dan Rekayasa Lalu Lintas Pada Kawasan Simpang 3 (Tiga) Jembatan Ngujang - Jalan Raya Ngantru - Hartono Hartono; Ari Widi Wibowo; Fadjar Lestari (Jurnal Penelitian Transportasi Darat, 2021)
ABSTRACTStudy of Traffic Management and Engineering at the Simpang 3 (Three) Ngujang Bridge - Jalan Raya Ngantru Area: Along with the development of community activities, the increase and mobility of the population and the growth of private vehicle ownership which is not followed by the growth of transportation infrastructure (roads, parking, etc.) in Tulungagung Regency, resulted in transportation problems in the Regency. One of them happened on the Ngujang Bridge, Ngantru Road Street, there was a bottle neck on the road section on the Ngujang Bridge where on the north side of the bridge there was an intersection. This condition often causes traffic delays on the bridge body. In addition, the condition of the wide and smooth Ngantru highway encourages many drivers to drive their vehicles at high speed, resulting in a high number of accidents on this road segment. MKJI analysis is to be able to carry out planning, design, and traffic operation of signalized intersections, unsignalized intersections and sections of braids and roundabouts, road sections (urban roads, out-of-town roads and expressways) This manual is primarily designed so that users can estimate the traffic behavior of a facility under certain traffic conditions, geometrics and environmental conditions. Based on the performance level of the Ngujang intersection under existing conditions, it is necessary to evaluate the performance of the intersection, add road equipment and enforce laws such as boundary signs speed.Keywords: Intersection; Service of Level; Traffic Delay; Transportation.ABSTRAKSeiring berkembangnya aktifitas masyarakat, pertambahan dan mobilitas penduduk dan pertumbuhan kepemilikan kendaraan pribadi yang tidak diikuti dengan pertumbuhan prasarana transportasi (jalan, parkir, dan lain-lain) di Kabupaten Tulungagung, berakibat adanya permasalahan transportasi di Kabupaten tersebut. Salah satunya terjadi di Jembatan Ngujang, Jalan Raya Ngantru ini terdapat bottle neck pada ruas jalan di Jembatan Ngujang yang pada sisi utara mulut jembatan terdapat simpang tiga. Kondisi ini sering menimbulkan tundaan lalu lintas di atas badan jembatan. Selain itu, kondisi  jalan raya Ngantru yang lebar dan mulus mendorong banyak pengemudi memacu kendaraannya dengan kecepatan tinggi sehingga mengakibatkan tingginya angka kecelakaan di ruas jalan ini. analisa MKJI adalah untuk dapat melaksanakan Perancangan (planning), Perencanaan (design), dan pengoperasionalan lalu-lintas (traffic operation) simpang bersinyal, simpang tak bersinyal dan bagian jalinan dan bundaran, ruas jalan (jalan perkotaan, jalan luar kota dan jalan bebas hambatan. Manual ini direncanakan terutama agar pengguna dapat memperkirakan perilaku lalulintas dari suatu fasilitas pada kondisi lalulintas, geometrik dan keadaan lingkungan tertentu. Berdasarkan tingkat kinerja simpang tiga Ngujang pada kondisi eksisting maka perlu dilakukan evaluasi terhadap kinerja simpang, penambahan perlengkapan jalan serta penegakan hukum seperti rambu batas kecepatan.Kata Kunci: Simpang; Tingkat Pelayanan; Tundaan Lalu Lintas; Transportasi